If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14n + -6 + -5n + -29 = 0 Reorder the terms: -6 + -29 + 14n + -5n = 0 Combine like terms: -6 + -29 = -35 -35 + 14n + -5n = 0 Combine like terms: 14n + -5n = 9n -35 + 9n = 0 Solving -35 + 9n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 9n = 0 + 35 Combine like terms: -35 + 35 = 0 0 + 9n = 0 + 35 9n = 0 + 35 Combine like terms: 0 + 35 = 35 9n = 35 Divide each side by '9'. n = 3.888888889 Simplifying n = 3.888888889
| 3[x-4]=8[x-9] | | 10x+3x+8x= | | 5times=135 | | (x-1)(x^2+5x-6)= | | (6x+6)+(10x-30)= | | 2x^2-6x=80 | | 7-(4n-8)=7-5n | | 5[x-4]=2[x-7] | | 9x+4+3+8=12 | | 7x^2+76x=8 | | 18c-4-2c+12= | | 54=x+5x | | 8u-6u=6 | | 5[x-3]=4[x+2] | | 11=4+v | | 12p+6=8p+30 | | 9x-30=2x+5 | | 47+11x=-30 | | (4x+3)=25 | | 179=6-u | | X-5.67=8.2 | | 12+x=3(3-2x) | | 47+11x=30 | | x(2x+1)=5x+1 | | 4[2-x]=5[x-2] | | -6u=4 | | 6(n-4)-(3-5n)=10n | | 5x=3-2y | | 8*x^3-6*x-1=0 | | 47+11=30 | | 3-1x=1 | | 3(8n-2)+8=(5+2n)-38+8n |